2014
DOI: 10.1039/c4tc01681e
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous tunable visible to near infrared emission in the Mn2+-doped spinel MgGa2O4 and room-temperature upconversion in the Mn2+ and Yb3+-codoped spinel

Abstract: In contrast to common visible emission, an anomalous near-infrared emission at 790 nm has been demonstrated in spinel structure MgGa2O4:Mn2+ with heavy Mn2+ doping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Obviously, the formation of Mn 2+ Mn 2+ dimers requires a the critical distance of ≈5 Å between two Mn 2+ ions . On average, higher doping concentration leads to lower distance among the activators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the formation of Mn 2+ Mn 2+ dimers requires a the critical distance of ≈5 Å between two Mn 2+ ions . On average, higher doping concentration leads to lower distance among the activators.…”
Section: Resultsmentioning
confidence: 99%
“…However, emissions from the assumed superexchange reaction occurs outside the sensitivity range of the human eye, so it is irrelevant for applications in illumination or display . Furthermore, because a significant part of the incoming excitation energy is converted to infrared emission in this system, the output in visible (Vis) luminescence is comparably low …”
Section: Introductionmentioning
confidence: 99%
“…The authors provided concrete evidence that lanthanide-doped nanocrystals have exceptionally high photostability against laser beam illumination (100-170 W cm À2 ) for 4 h. In a recent work by the same group, they suggested that the high photostability against photobleaching is a general characteristic of the UC nanocrystals, regardless of whether different host materials or core-shell strategies are implemented. 78 In both T 1g (G) -6 A 1g (S) [188][189][190] cases, superior photophysical stability of UC nanocrystals was further verified under high power density excitation up to 3 Â 10 6 W cm À2 (Fig. A high power density of 10 6 W cm À2 can be generated by focusing laser beam into a tiny volume with a diameter of less than 1 mm.…”
Section: Excitation By Continuous-wave (Cw) Lasermentioning
confidence: 99%
“…It was suggested that tetrahedrally (weak crystal field) and octahedrally (strong crystal field) coordinated Mn 2+ ions tend to give rise to green and orange-to-red emission, respectively. [25][26][27][28] We hypothesized that a continued increase in Ca 2+ doping concentration might lead to variations in the crystal field around Mn 2+ ions. To prove this, we performed extended www.advopticalmat.de X-ray absorption fine structure (EXAFS) measurement of NaGdF 4 :Ca/Mn (x/30 mol%) nanoparticles (x = 5 and 40) ( Figure 3b).…”
Section: Tuning Long-lived Mn(ii) Upconversion Luminescence Through Amentioning
confidence: 99%